2018
DOI: 10.1111/cpr.12460
|View full text |Cite
|
Sign up to set email alerts
|

Topographical cues of direct metal laser sintering titanium surfaces facilitate osteogenic differentiation of bone marrow mesenchymal stem cells through epigenetic regulation

Abstract: Topographical cues of DMLS surfaces have greater potential for the induction of osteogenic differentiation of BMSCs than SLA and Ti surfaces both in vitro and in vivo. A potential epigenetic mechanism is that the appropriate topography allows rapid H3K27 demethylation and an increased H3K4me3 level at the promoter region of osteogenesis-associated genes during the osteogenic differentiation of BMSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…In these cases, selective localization of Ash1l may coordinately modify local H3K4 methylation kinetics in the region of gene promoters. Including Ash1l, the overall 11 kinds of H3K4 methyltransferases [50] may coordinately promote H3K4me3 enrichment at osteogenic genes in tune during osteogenic differentiation [51]. It is reported that Ash1l and Mll1 cooperate to methylate H3K4 at actively transcribed region [15,52].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, selective localization of Ash1l may coordinately modify local H3K4 methylation kinetics in the region of gene promoters. Including Ash1l, the overall 11 kinds of H3K4 methyltransferases [50] may coordinately promote H3K4me3 enrichment at osteogenic genes in tune during osteogenic differentiation [51]. It is reported that Ash1l and Mll1 cooperate to methylate H3K4 at actively transcribed region [15,52].…”
Section: Discussionmentioning
confidence: 99%
“…To mimic this environment, it is also of great significance to manufacture intraosseous implants with hierarchical micro-nano surface topography (Shah et al, 2018;Cui et al, 2019;Zhang et al, 2019). In our previous work, we fabricated titanium surfaces with hierarchical microprotrusionnanonotch topography using direct metal laser sintering technique together with acid etching treatment, which could promote osteogenic differentiation of stem cells (Zheng et al, 2018). To enable further performance improvements, hierarchical microgroove-nanopore topography was fabricated by selective laser melting (SLM) technique combined with alkali heat treatment (AHT) because of higher fabricating efficiency and less consumption of raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…The component and hierarchical structure are the key issues need to be simulated when constructing the biomimetic material (Wegst et al, 2015;Wingender et al, 2016;Ling et al, 2018;Zheng et al, 2018). ACP was a critical component and abundant in woven bone besides collagen and nHA.…”
Section: Discussionmentioning
confidence: 99%